Analisis Cacat Produk Baju Muslim Di Pd. Yarico Collection Menggunakan Metode Failure Mode And Effect Analysis - Masrofah, Isma; Firdaus, Hariswan (Jurnal Media Teknik dan Sistem Industri, 2018)
Abstract—Yarico Collection Trad. Co. is a company engaged in clothing convection for the last 12 years. One of the problems faced by this company is the number of defective products that exceed the defect tolerance limits set by the company. The company sets a defect limit of 1% of the total production, while in the field the number of defects is 3%. This study aims to find out the priorities of the causes of disability and find out how to reduce the number of defects related to women's Muslim clothing that occur in the cutting process of 20 units from 1250 units, the process of sewing or unifying clothes by 22 units out of 1250 units, the process of closing down 19 units out of 1250 unit, and the pressing process is 14 units out of 1250 units. The researcher used the Failure Mode Effects Analysis (FMEA) method to obtain the most dominant failure mode of production process, the calculation of Risk Priority Number (RPN) generated in the pressing process with RPN 504 value, sewing process with RPN 448 value, the process of stitching stitches with RPN value 392, and the cutting process with the RPN value 384. From the results of the study obtained several proposals according to the highest RPN value to reduce the number of product defects, including: for cutting defects by adding lighting and periodic machine maintenance, for sewing defects scheduled and the use of components that are standard, for defects in obras are made machine maintenance scheduling, the use of spare parts that are standardized, and using a strongbranded needle, for defects in the pressing process by doing good engine maintenance and providing training to workers with use temperature machine according to the type of fabric. Keywords ; product defect, quality improvement, FMEA, RPN Abstrak— PD. Yarico Collection merupakan perusahaan yang bergerak dalam bidang konveksi pakaian selama 12 tahun terakhir. Salah satu permasalahan yang dihadapi oleh perusahaan ini yaitu jumlah produk cacat yang melebihi batas tolerasi cacat yang di tetapkan oleh perusahaan. Perusahaan menetapkan batas cacat yaitu 1 % dari jumlah peroduksi sedangkan dilapangan jumlah cacat sebesar 3 %. Penelitian bertujuan untuk mengatehaui prioritas penyebab cacat dan mengetahui bagaimana cara menurunkan jumlah cacat terkait baju muslim wanita yang terjadi pada proses cutting sebesar 20 unit dari 1250 unit, proses penjahitan atau penyatuan baju sebesar 22 unit dari 1250 unit, proses obras sebesar 19 unit dari 1250 unit, dan pada proses pressing sebesar 14 unit dari 1250 unit. Peneliti menggunakan metode Failure Modes Efect Analysis (FMEA) sehingga didapat mode kegagalan paling dominan diproses produksi, hasil perhitungan Risk Priority Number (RPN) yang dihasilkan pada proses pressing dengan nilai RPN 504, proses penjahitan dengan nilai RPN 448, proses obras jahitan dengan nilai RPN 392, dan pada proses cutting dengan nilai RPN 384. Dari hasil penelitian didapat beberapa usulan sesuai nilai RPN tertinggi untuk menurunkan jumlah cacat produk, diantaranya : untuk cacat cutting dengan melakukan penambahan penerangan serta melakukan perawatan mesin secara berkala, untuk cacat penjahitan melakukan perawatan mesin secara terjadwal serta penggunaan komponen yang sesuai standard, untuk cacat pada obras dibuat penjadwalan perawatan mesin, penggunaan spare part yang sesuai standar, dan menggunakan jarum obras yeng berbahan kuat, untuk cacat pada proses pressing dengan melakukan perawatan mesin yang baik serta memberika pelatihan kepada pekerja dengan penggunaan suhu mesin sesuai jenis kain.Kata Kunci : Cacat Produk, Quality Improvement, FMEA, RPNa